The mediating role of meaning of life and theism in the relationship between a person’s attachment style and premature mourning in women with MS - Moharari, Zahra; Esmaeili, Masoumeh (Psychology of Woman Journal, 2020)
This research was conducted to determine the mediating role of the meaning of life and belief in God in the relationship between a person’s attachment style and premature grief in people with M.S. The current descriptive and correlational research and the statistical population of the research were all women members of the M.S. Association of Shiraz in 1400. Among the statistical population, 205 women from M.S. patients were selected and studied by the available sampling method. To collect data, questionnaires of meaning in life were used by Steiger et al. (2006), premature mourning of Dehghani (2012), Khoda Bavari Beck and MacDonald (2004), and Hazen and Shiver (1985) attachment styles. After collecting and extracting data, participants’ scores were analyzed using Pearson’s correlation coefficient and path analysis. The results showed a significant negative correlation (0.01) between the meaning of life, belief in God, and secure attachment style with premature grief and a positive correlation between avoidant attachment style and ambivalent attachment style with premature grief (0.05). Also, the indirect effects of mediating variables showed that the meaning of life and belief in God significantly mediate the relationship between a person’s attachment style and premature grief in people with M.S.